Application of Health Belief Model on Child’s Dental Visit Postponement during the COVID-19 Pandemic - Setiawan, Arlette Suzy; Zubaedah, Cucu (European Journal of Dentistry, 2020)
Objective The aim of this article is to analyze parental perception on child’s dental visit postponement using health belief model (HBM) during the pandemic of COVID-19.Materials and Methods Cross-sectional survey design was chosen with a purposive sample recruited online by distributing questionnaires consisting 26 items of HBM construct. Data were analyzed descriptively by SPSS version 22.Result A total 111 respondents participated in the study. Respondents perception were found indifferent in perceived susceptible (X̄ = 3.07), perceived severity (X̄ = 2.99), and perceived barrier (X̄ = 3.38). Whilst confirmed in perceived benefit (X̄ = 2.54), cue of action (X̄ = 2.05), self-efficacy (X̄ = 2.08), and locus of control (X̄ = 2.88).Conclusion This study provided evidence that HBM is applicable to children's dental visit postponement during the pandemic of COVID-19.
Keywords: health belief model; dental visit postponement; COVID-19; pandemic